Reproductive-dependent effects of B vitamin deficiency on lifespan and physiology - Yu, Guixiang; Liu, Shaowei; Yang, Kun; Wu, Qi (Frontiers in Nutrition, 2023)
B vitamins constitute essential micronutrients in animal organisms, executing crucial roles in numerous biological processes. B vitamin deficiency can result severe health consequences, including the impairment of reproductive functions and increased susceptibility to age-related diseases. However, the understanding of how reproduction alters the requirements of each individual B vitamins for healthy aging and lifespan remains limited. Here, utilizing Drosophila as a model organism, we revealed the substantial impacts of deficiencies in specific B vitamins on lifespan and diverse physiological functions, with the effects being significantly shaped by reproductive status. Notably, the dietary absence of VB1, VB3, VB5, VB6 or VB7 significantly decreased the lifespan of wild-type females, yet demonstrated relatively little effect on ovo D1 infertile mutant females' lifespan. B vitamin deficiencies also resulted in distinct impacts on the reproduction, starvation tolerance and fat metabolism of wildtype females, though no apparent effects were observed in the infertile mutant females. Moreover, a deficiency in VB1 reshaped the impacts of macronutrient intervention on the physiology and lifespan of fertile females in a reproductive-dependent manner. Overall, our study unravels that the reproductive status of females serves as a critical modulator of the lifespan and physiological alterations elicited by B-vitamin deficiencies.